Quartz Crystal Microbalance With Dissipation Monitoring: A Powerful Method to Predict the in vivo Behavior of Bioengineered Surfaces - Tonda-Turo, Chiara; Carmagnola, Irene; Ciardelli, Gianluca (Frontiers in Bioengineering and Biotechnology, 2018)
The Quartz Crystal Microbalance with monitoring of dissipation (QCM-D) is a tool to measure mass and viscosity in processes occurring at or near surfaces, or within thin films. QCM-D is able to detect extremely small chemical, mechanical and electrical changes taking place on the sensor surface and to convert them into electrical signals which can be investigated to study dynamic process. Surface nanotopography and chemical composition are of pivotal importance in biomedical applications since interactions of medical devices with the physiological environment are mediated by surface features. This review is intended to provide readers with an up-to-date summary of QCM-D applications in the study of cell behavior and to discuss the future trends for the use of QCM-D as a high-throughput method to study cell/surface interactions overcoming the current challenges in the design of biomedical devices.